Social Mechanisms in Epidemiological Publications on Small-Area Health Inequalities—A Scoping Review - Zolitschka, Kim Alexandra; Razum, Oliver; Breckenkamp, Jürgen; Sauzet, Odile (Frontiers in Public Health, 2019)
Background: Small-area social mechanisms – social processes involving the social environment around the place of residence – may be playing a role in the production of health inequalities. Understanding how small-area health inequalities (social environment affects health and consequently contribute to inequalities between areas) are generated and the role of social mechanisms in this process may help defining interventions to reduce inequalities. In mediation and pathway analyses, social mechanisms need to be treated as processes or factors. We aimed to identify which types of social mechanisms explaining the process leading from small-area characteristics to health inequalities have been considered and investigated in epidemiological publications and to establish how they have been operationalised. Methods: We performed a scoping review for social mechanisms in the context of small-area health inequalities in the database PubMed. Epidemiological publications identified were categorized according to the typology proposed by Galster (social networks, social contagion, collective socialisation, social cohesion, competition, relative deprivation, parental mediation). Furthermore, we assessed whether the mechanisms were operationalised at the micro or macro level and whether mechanisms were considered as processes or merely as exposure factors. Results: We retrieved 1019 studies, 15 thereof were included in our analysis. Eight forms of operationalisation were found in the category social networks and another nine in the category social cohesion. Other categories were hardly represented. Furthermore, all studies were cross-sectional and did not consider mechanisms as processes. Except for one, all studies treated mechanisms merely as factors whose respective association to health outcomes was tested. Conclusion: In epidemiological publications, social mechanisms in studies on small-area effects on health inequalities are not operationalised as processes in which these mechanisms would play a role. Rather, the focus is on studying associations. To understand the production of health inequalities and the causal effect of social mechanisms on health, it is necessary to analyse mechanisms as processes. For this purpose, methods such as complex system modelling should be considered.